From Inception to Interface: Ontologies, Data Modelling, and Linked Data for Online Exhibition-Making. - Rodwell, Julia; Whitelaw, Mitchell (Parergon, 2024)
The article discusses the creation of an online exhibition titled "Beyond the Book: A Digital Journey through the Treasures of the Emmerson Collection." It explores the use of CIDOC CRM, a cultural heritage ontology, and Linked Data to model and publish information about the Emmerson Collection. It aims to communicate both the material richness of the items and the broader historical context of books through a combination of text, images, and interactive data.